2016
DOI: 10.1038/ncomms10398
|View full text |Cite
|
Sign up to set email alerts
|

The puzzling Venusian polar atmospheric structure reproduced by a general circulation model

Abstract: Unlike the polar vortices observed in the Earth, Mars and Titan atmospheres, the observed Venus polar vortex is warmer than the midlatitudes at cloud-top levels (∼65 km). This warm polar vortex is zonally surrounded by a cold latitude band located at ∼60° latitude, which is a unique feature called ‘cold collar' in the Venus atmosphere. Although these structures have been observed in numerous previous observations, the formation mechanism is still unknown. Here we perform numerical simulations of the Venus atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 36 publications
(58 reference statements)
7
69
0
Order By: Relevance
“…In the present study, we compare the radio occultation measurements with GCM simulations to understand the atmospheric dynamics of the observational results. A Venus GCM used in this study is AFES‐Venus, a full nonlinear GCM with simplified physical processes for the Venus atmosphere (Sugimoto et al, , ), which has enabled us to reproduce the realistic zonal wind and temperature distributions of the Venus atmosphere (Sugimoto et al, ), the unique polar atmospheric structure such as the cold collar and warm polar regions (Ando et al, ), and short‐period temperature disturbances observed in the warm polar region (Ando et al, ). Recently, Sugimoto et al () succeeded in data assimilation by using the wind field data obtained in Venus Express mission.…”
Section: Comparison With Gcm Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we compare the radio occultation measurements with GCM simulations to understand the atmospheric dynamics of the observational results. A Venus GCM used in this study is AFES‐Venus, a full nonlinear GCM with simplified physical processes for the Venus atmosphere (Sugimoto et al, , ), which has enabled us to reproduce the realistic zonal wind and temperature distributions of the Venus atmosphere (Sugimoto et al, ), the unique polar atmospheric structure such as the cold collar and warm polar regions (Ando et al, ), and short‐period temperature disturbances observed in the warm polar region (Ando et al, ). Recently, Sugimoto et al () succeeded in data assimilation by using the wind field data obtained in Venus Express mission.…”
Section: Comparison With Gcm Resultsmentioning
confidence: 99%
“…In this study, we analyze the Akatsuki radio occultation data to investigate the local time dependence of the thermal structure of the upper atmosphere in the equatorial region and compare the results with numerical simulations by a Venus GCM. The GCM used in this study is a full nonlinear Venus GCM named AFES‐Venus (Ando et al, , ; Sugimoto et al, , ; Takagi et al, ), based on AFES 2 (Atmospheric GCM for the Earth Simulator version 2; Enomoto et al, ; Ohfuchi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since in our model the planet Venus is assumed to rotate toward the same direction as the Earth, note that the zonal wind (superrotation) reproduced in our model also directs toward the east. Details of the model settings are described in Sugimoto et al [] and Ando et al [].…”
Section: Comparison To Gcmmentioning
confidence: 99%
“…Since in our model the planet Venus is assumed to rotate toward the same direction as the Earth, note that the zonal wind (superrotation) reproduced in our model also directs toward the east. Details of the model settings are described in Sugimoto et al [2014b] and Ando et al [2016]. The model atmosphere reached quasi-steady states within approximately 1 Earth year, and the quasi-steady states were maintained for more than 10 Earth years [Sugimoto et al, 2014b].…”
Section: Setup Of Gcmmentioning
confidence: 99%
See 1 more Smart Citation